2009
DOI: 10.1007/dcr.0b013e31819c9c08
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Complex Crohn's Disease on the Outcome of Laparoscopic Ileocecal Resection

Abstract: This large comparative study suggested that laparoscopic ileocolonic resection for complex Crohn's disease was feasible and safe with good postoperative outcomes. In our experience, complex Crohn's disease does not appear as a contraindication to a laparoscopic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(89 citation statements)
references
References 19 publications
2
80
0
6
Order By: Relevance
“…9 In another recent prospective study comparing complicated CD and uncomplicated CD undergoing laparoscopic ICR, a two-stage procedure with a temporary diverting stoma was performed in 39% for complex fistulizing CD (all of them being voluntarily performed). 8 Operative findings evidenced that the inflammatory process in patients who initially had an abscess or phlegmon diminished after 2 weeks of bowel rest. It is therefore likely that our strategy of pre-operative management allowed ICR to be performed with primary anastomosis in circumstances that might have otherwise required a two-stage procedure with diverting stoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 In another recent prospective study comparing complicated CD and uncomplicated CD undergoing laparoscopic ICR, a two-stage procedure with a temporary diverting stoma was performed in 39% for complex fistulizing CD (all of them being voluntarily performed). 8 Operative findings evidenced that the inflammatory process in patients who initially had an abscess or phlegmon diminished after 2 weeks of bowel rest. It is therefore likely that our strategy of pre-operative management allowed ICR to be performed with primary anastomosis in circumstances that might have otherwise required a two-stage procedure with diverting stoma.…”
Section: Discussionmentioning
confidence: 99%
“…Abscess, phlegmon or fistulas are not contraindications to a successful laparoscopic ICR. 8,26 Several authors have reported fewer complications associated with the laparoscopic approach. [26][27][28] Nevertheless, the nature of complicated CD can render surgery challenging and the technical difficulties encountered are more pronounced with laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many patients a minimally invasive approach is feasible and safe, though has been associated with longer operative times, higher conversion rates, and increased stoma use for complex Crohn's patients including fistula. 17 At the time of surgery, a small probe placed into the external opening will often allow better localization of the tract during the dissection of the bowel. Although I prefer a medial-to-lateral approach in both the open and laparoscopic approaches for lesions in the ileocolic region, the degree of inflammation will be the major determining factor.…”
Section: Spontaneous Ecf In Inflammatory Bowel Disease (Crohn's Disease)mentioning
confidence: 99%
“…Entretanto, as contra-indicações diminuem conforme evoluem a perícia cirúrgica e os equipamentos 6 .…”
Section: Contra-indicaçõesunclassified